IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL TERHADAP PENGALAMAN NILAI PANCASILA PADA SISWA KELAS V DI SD 4 KARANGMALANG - Janita Putri Dwihana; Aurellyna Lintang Permata Sari; Nella Marsha Aulia; Fina Fakhriyah; Erik Aditia Ismaya (LPPM Universitas Cipta Mandiri, 2025)
This study aims to explain the implementation of Contextual Teaching and Learning (CTL) model in instilling and strengthening the understanding of Pancasila values among fifth grade students at SD 4 Karangmalang. This research uses a combination method that combines qualitative and quantitative approaches (or vice versa). This research used a qualitative descriptive method, with the aim of describing in detail the processes, experiences, and reactions of students and teachers during the implementation of contextualized learning. Data collection was done through observations, interviews, and document collection to gain a thorough understanding of how Pancasila values are applied in students' daily lives. The results indicated that the implementation of CTL can increase students' participation, understanding, and appreciation of Pancasila values in daily life. The majority of students showed good to excellent achievement in understanding the values of Pancasila, and there were improvements in discussion activities, group collaboration, and reflection on direct experience. The CTL model proved effective in building students' character and behavior in accordance with the noble values of Pancasila, although adaptive strategies are needed to reach all students.